Diversity and succession of autotrophic microbial community in high-elevation soils along deglaciation chronosequence - Liu, Jinbo; Kong, Weidong; Zhang, Guoshuai; Khan, Ajmal; Guo, Guangxia; Zhu, Chunmao; Wei, Xiaojie; Kang, Shichang; Morgan-Kiss, Rachael M. (FEMS microbiology ecology, 2016)
Global warming has resulted in substantial glacier retreats in high-elevation areas, exposing deglaciated soils to harsh environmental conditions. Autotrophic microbes are pioneering colonizers in the deglaciated soils and provide nutrients to the extreme ecosystem devoid of vegetation. However, autotrophic communities remain less studied in deglaciated soils. We explored the diversity and succession of the cbbL gene encoding the large subunit of form I RubisCO, a key CO2-fixing enzyme, using molecular methods in deglaciated soils along a 10-year deglaciation chronosequence on the Tibetan Plateau. Our results demonstrated that the abundance of all types of form I cbbL (IA/B, IC and ID) rapidly increased in young soils (0–2.5 years old) and kept stable in old soils. Soil total organic carbon (TOC) and total nitrogen (TN) gradually increased along the chronosequence and both demonstrated positive correlations with the abundance of bacteria and autotrophs, indicating that soil TOC and TN originated from autotrophs. Form IA/B autotrophs, affiliated with cyanobacteria, exhibited a substantially higher abundance than IC and ID. Cyanobacterial diversity and evenness increased in young soils (<6 years old) and then remained stable. Our findings suggest that cyabobacteria play an important role in accumulating TOC and TN in the deglaciated soils. Autotrophic microorganisms rapidly colonized young deglaciated soils and their abundance positively correlated with total organic carbon and total nitrogen, suggesting that soil TOC and TN originated from autotrophs.